Comparison of two dosing methods for immediate administration of tolvaptan in acute decompensated heart failure. Issue 3 (September 2018) - Oguri, Mitsutoshi; Ishii, Hideki; Ohguchi, Shiou; Takahara, Kunihiko; Kawamura, Yoshihiro; Yokoi, Yuki; Izumi, Kazuhiro; Takahashi, Hiroshi; Kamiya, Haruo; Murohara, Toyoaki
Highlights: Two dosing regimens were compared: once-daily 7.5 mg and twice-daily 3.75 mg. Earlier decongestion could be expected with the early administration of tolvaptan. The serial change in congestion scores was similar according to dosing regimens. Abstract: Background: The clinical dosing method for tolvaptan in patients with acute heart failure (HF) is still unclear. We aimed to compare the differences in clinical effect between two dosing regimens: once-daily 7.5 mg and twice-daily 3.75 mg. Methods: In this randomized trial, tolvaptan was administered within 12 h from hospital admission. The primary outcome was the serial change in congestion scores measured every day from enrollment until dosing day 7. Outcomes including safety parameters were also evaluated. Results: The subjects were assigned to either the once-daily 7.5 mg dosing regimen ( N  = 15) or the twice-daily 3.75 mg dosing regimen ( N  = 16). The time-course changes in body weight, serum sodium and creatinine levels, systolic blood pressure, daily urine output, and congestion scores were similar between the two groups. In the twice-daily 3.75 mg dosing group, the serum sodium levels on days 3 and 4 were significantly ( p  < 0.05) increased compared with those on day 1. The congestion scores significantly ( p  < 0.05) decreased from day 2 to day 7 in both groups compared with those on day 1. However, the difference in the serial change in the congestion scores did not reach statistical significance. Conclusions: Our present results suggest that the early administration of tolvaptan within 12 h after hospital admission significantly improved congestion from the first day after administration by either dosing regimen, i.e. once-daily 7.5 mg or twice-daily 3.75 mg in patients with acute HF.